Helical Micro-Hole Drilling Of Chemically Strengthened Glass Using Capsule-Shaped Electroplated Diamond Tool - Mizobuchi, Akira; Abdul Aziz, Mohd Sanusi; Kasim, Mohd Shahir; Mohamad, Effendi; Salleh, Mohd Rizal; Raja Abdullah, Raja Izamshah; Ishida, Tohru (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
This study investigates the micro-hole drilling performance of chemically strengthened glass plate by using a capsule-shaped electroplated diamond tool and the helical drilling method. Three different helical pitch conditions were tested to drill holes with a diameter of 1 mm. The number of drilled holes, grinding force, and maximum crack size were measured along with the observation of the drilled holes to evaluate the performance of the micro-hole drilling. From the experimental results, it was found that as the size of helical pitch decreased, the number of drilled holes increases where the average grinding force generated becomes smaller. By using small helical pitch condition, 43 holes could be drilled but the maximum crack size generated at the outlet side of the drilled hole is not able to achieve the high-grade quality compared to the inlet side. The resultant grinding force generated when the tool tip nearing the outlet side of the glass plate has caused the large crack at a certain position on the outlet side.